2002
DOI: 10.1063/1.1417992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reflectivity inversion, α- and β-phase transitions and nanostructure formation in hydrogen activated thin Pd films on silicon based substrates

Abstract: Optically thin palladium metal films evaporated on different silicon based substrates are investigated following exposure to different concentrations of hydrogen gas in air. Laser modulated reflectance off the palladium surface of silicon oxide and silicon nitride substrates is used to recover information regarding the reflectivity inversion and α/β-phases of the palladium complex after both first and multiple gas cycling. Atomic force microscopy confirms the formation of metal nanostructures following exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…The PdH ␣ → ␤ phase transition occurs at a specific hydrogen concentration, typically ranging between 0.1% and 2%, which is dependent on the palladium film thickness, alloying element and quantity. The phase transition has been observed by many research groups and specifically a response time as long as 3600 s have been observed for an optical-based sensor and a factor of 100 increase (5 s as compared to 50 ms) in response time has been observed for a Pd nanoparticle electrical-based hydrogen sensor [9]. Furthermore, a reliable hydrogen sensor is required for the sensing applications that are envisioned in a future hydrogen based economy and historically Pd-based hydrogen sensors have suffered from poor reliability due to material instabilities resulting from the large volume changes that occur during the PdH ␣ → ␤ phase transition [10].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The PdH ␣ → ␤ phase transition occurs at a specific hydrogen concentration, typically ranging between 0.1% and 2%, which is dependent on the palladium film thickness, alloying element and quantity. The phase transition has been observed by many research groups and specifically a response time as long as 3600 s have been observed for an optical-based sensor and a factor of 100 increase (5 s as compared to 50 ms) in response time has been observed for a Pd nanoparticle electrical-based hydrogen sensor [9]. Furthermore, a reliable hydrogen sensor is required for the sensing applications that are envisioned in a future hydrogen based economy and historically Pd-based hydrogen sensors have suffered from poor reliability due to material instabilities resulting from the large volume changes that occur during the PdH ␣ → ␤ phase transition [10].…”
Section: Introductionmentioning
confidence: 87%
“…The Pd 0.6 Au 0.4 film has an alloy composition that is above the critical isotherm threshold (∼17 at.% Au) and thus does not experience an ␣ → ␤ phase transition, which has been shown to limit the response times of hydrogen sensors near the hydrogen LEL (0.1-2%) [14][15][16]. Subsequently for this particular Pd alloy film the response time will only be limited by background gas adsorption on the Pd alloy surface and its corresponding operation temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Kalli et al 21 studied the reflectivity of a Pd film varying from a thickness of 1 to 30 nm and characterized the α-and β-phase transitions after both single and multiple gas cycles from the reflectivity measurement. In particular, they demonstrated that the change of reflectivity depends on the Pd thickness and on the substrate.…”
Section: Characterization Of Pd Thin Filmmentioning
confidence: 99%
“…10). Simple index of refraction arguments proved sufficient to explain these results [26][27][28]. Moreover, structural changes of the palladium films were investigated using atomic force microscopy before and after hydrogen exposure, where nanostructure formation was highlighted as a possible means of fabricating nano-devices [29].…”
Section: Research Between and After The Kent Yearsmentioning
confidence: 99%